Enhancing staff motivation in "tough" periods: implications for business leaders. Issue 6 (6th May 2014) - Panagiotakopoulos, Antonios
Abstract : Purpose: – The purpose of the paper is to present a viewpoint based on an empirical study conducted by the author, which explored the motivational techniques used by 30 chief executive officers in the context of an advancing economy like Greece that faces a severe financial crisis and evaluated the impact of such motivational tools on staff performance. Design/methodology/approach: – The viewpoint is based on a quantitative survey of 30 Greek large organizations involving the leaders of the firms and 113 workers. In all, 143 responses were collected concerning the main motivational techniques used by the participant leaders and their impact on employee behavior. Findings: – Overall, the findings showed that in the short-term, both motivational models (i.e. "inspirational" versus "fear") may lead to effective organizational performance. However, the main difference appears to be related to the long-term impact of each model on firm performance. In particular, the findings indicated that "fear motivation" is more likely to lead to poor firm performance in the long-run compared to "inspirational motivation" due to increased staff absenteeism and turnover. Practical implications: – The core implication of the study is that "fear motivation" should be reconsidered by business leaders, as the particular motivational approach adopted has been based on a limited understanding around its overall impact on employee performance. As the analysis revealed, a motivational model focused around empowerment, trust and individual development may lead to better organizational results. Originality/value: – It informs the existing management literature about the impact of different motivational patterns on employee performance, where our knowledge is limited.